Group 2 ILCs: A way of enhancing immune protection against human helminths?. (12th July 2017) - Nausch, N.; Mutapi, F.
Summary: Group 2 innate lymphoid cells (ILC2s) play crucial roles in type 2 immune responses associated with allergic and autoimmune diseases, viral and helminth infections and tissue homoeostasis. Experimental models show that in helminth infections ILC2s provide an early source of type 2 cytokines and therefore are essential for the induction of potentially protective type 2 responses. Much of our knowledge of ILC2s in helminth infections has come from experimental mouse models with very few studies analysing ILC2s in natural human infections. In attempts to harness knowledge from paradigms of the development of protective immunity in human helminth infections for vaccine development, the role of ILC2 cells could be pivotal. So far, potential vaccines against human helminth infections have failed to provide effective protection when evaluated in human studies. In addition to appropriate antigen selection, it is apparent that more detailed knowledge on mechanisms of induction and maintenance of protective immune responses is required. Therefore, there is need to understand how ILC2 cells induce type 2 responses and subsequently support the development of a protective immune response in the context of immunizations. Within this review, we summarize the current knowledge of the biology of ILC2s, discuss the importance of ILC2s in human helminth infections and explore how ILC2 responses could be boosted to efficiently induce protective immunity.